Golf players as a customer segment: the influence of handicap level and residency in customer satisfaction and expenditure - Ricardo Macías; José Bonal; Iyán Iván-Baragaño; Jairo León-Quismondo; Marta Herráiz; Mercedes Leguina; Javier del Arco; Benito Pérez-González; Pablo Burillo; Álvaro Fernández-Luna (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
Segmentation has been proven to be one of the best tools to facilitate sports entities' achievement of their goals. The objective of this research was to analyze the influence on customer expenditure and satisfaction for an elite golf event based on segmentation variables such as residence (local vs visitor) and handicap level of the attendees (spectator vs spectator-player). In addition, this research aimed to establish a multivariate model that allows predicting the place of residence and the handicap based on the interaction of the analyzed variables, with the intention to establish a behaviour pattern based on these variables for those attending an elite golf tournament. Results revealed that attendees with a golf handicap exhibited higher satisfaction levels and were more likely to recommend and spend at golf events. On the other hand, non-handicap spectators and those attendees from outside Madrid displayed higher economic expenditure, indicating the importance of meeting their specific needs to achieve positive economic impact results. The decision tree models provided insights into attendee behavior, identifying factors influencing their satisfaction and likelihood to attend again. Factors including future attendance intention, satisfaction with the food court variety, and spending on accommodation and souvenirs were found to be significant predictors of residency and handicap level. In conclusion, this research contributes to the understanding of customer behavior at elite golf events, offering practical implications for event organizers and sport managers.